Functional Characterization of Odorant Binding Protein 27 (RproOBP27) From Rhodnius prolixus Antennae - Oliveira, Daniele S.; Brito, Nathália F.; Franco, Thiago A.; Moreira, Monica F.; Leal, Walter S.; Melo, Ana C. A. (Frontiers in Physiology, 2018)
Olfactory proteins mediate a wide range of essential behaviors for insect survival. Odorant binding proteins (OBPs) are small soluble olfactory proteins involved in the transport of odor molecules (=odorants) through the sensillum lymph to odorant receptors, which are housed on the dendritic membrane of olfactory sensory neurons also known as olfactory receptor neurons. Thus, a better understanding of the role(s) of OBPs from Rhodnius prolixus, one of the main vectors of Chagas disease, may ultimately lead to new strategies for vector management. Here we aimed at functionally characterize OBPs from R. prolixus. Genes of interest were selected using conventional bioinformatics approaches and subsequent quantification by qPCR. We screened and estimated expression in different tissues of 17 OBPs from R. prolixus adults. These analyses showed that 11 OBPs were expressed in all tissues, whereas six OBP genes were specific to antennae. Two OBP genes, RproOBP6 and RproOBP13, were expressed in both male and female antennae thus suggesting that they might be involved in the recognition of semiochemicals mediating behaviors common to both sexes, such host finding (for a blood meal). Transcripts for RproOBP17 and RproOBP21 were enriched in female antennae and possibly involved in the detection of oviposition attractants or other semiochemicals mediating female-specific behaviors. By contrast, RproOBP26 and RproOBP27 might be involved in the reception of sex pheromones given that their transcripts were highly expressed in male antennae. To test this hypothesis, we silenced RproOBP27 using RNAi and examined the sexual behavior of the phenotype. Indeed, adult males treated with dsOBP27 spent significantly less time close to females as compared to controls. Additionally, docking analysis suggested that RproOBP27 binds to putative sex pheromones. We therefore concluded that RproOBP27 might be a pheromone-binding protein.